The Shadowlands - Charman, Katrina; Tondora, Judit (2019)
Tag the owl, Skyla the squirrel, and Blaze the firehawk are searching for the final piece of the magical Ember Stone that will hopefully save Perodia from the evil vulture Thorn, and their quest has led them to the Howling Caves in Valor Wood--but they do not know if the stone will actually be there, or what will be waiting for them when they emerge into the spreading darkness.
Grades 1-3.
Grade 2.
Keywords: Owls -- Juvenile fiction; Squirrels -- Juvenile fiction; Animals, Mythical -- Juvenile fiction; Quests (Expeditions) -- Juvenile fiction; Magic -- Juvenile fiction; Adventure stories; Owls -- Fiction; Squirrels -- Fiction; Animals, Mythical -- Fiction; Magic -- Fiction; Adventure and adventurers -- Fiction; Fantasy; Action and adventure fiction